Prognostic value of CD3, CD4, CD8 and CD 68 in high-grade diffuse astrocytomas, the transformation of an immune profile in recurrent tumors - Chertenko, Taisia; Yakovtsova, Irina (Journal of Education, Health and Sport, 2018)
Introduction and purpose. Immunotherapy has shown good results in the treatment of other cancers. There is a lack of data about the role of the immune system in high-grade glioma development. Moreover, the available data is ambiguous. Our recent study was aimed to clarify the prognostic value of T-cell and macrophage infiltration in high grade diffuse astrocytic tumors. In addition, we also investigated the changes in immune cell infiltration in paired primary and recurrent tumors. Methods. This study included 45 tumor samples that were collected from 15 patients without recurrence within 1 year after the surgery and from 15 patients who experienced a recurrence within 1 year after the surgery (30 paired samples). Immunohistochemistry with primary antibody CD3, CD4, CD8 and CD68 was used in our study. We marked lack of immune cell infiltration or single cell infiltration as “1” in our study and moderate or high infiltration as “2”. Results. CD68 “2” expression in tumor tissue is a significant independent factor of the worse prognosis (Fisher’s exact p-value=0,037). The significantly better prognosis was given to patients with such immune patterns as CD3 “1”/CD4 “2”/CD8 “2” and CD3 “1”/CD4 “2”/CD68 “2” (Fisher’s exact p-value=0,01869 and 0,01392 respectively). We also found that solid tumors with CD3 “2”/CD8 “1” and CD8 “1”/CD68 “2” immune had a significantly worse prognosis (Fisher’s exact p-value= 0,04981 in both groups). In relapsed tumors, we observed a significant increase of CD8-cell infiltration (McNemar test p-value=0,01343;p <0,05) that probably may be a result of treatment with temozolomide. Conclusion. Our findings confirmed the fact that immune cell infiltration may play an important role in brain tumor development. Further study in larger groups may lead to a better understanding of different immune profiles of glial tumors and to development of their targeted immunotherapy.